Florida 4-H Exploration: Careers in Horticulture - Marguerite Beckford; Sarah Davis; Kristie Popa; Marnie Ward (EDIS)
This publication highlights some of the many career pathways in horticulture. 4-H youth and 4-H club leaders can use the document to explore potential career interests. Written by Marguerite Beckford, Sarah Davis, Kristie Popa, and Marnie Ward, and published by the Florida 4-H Youth Development Program, UF/IFAS Extension, September 2023.